Low Temperature Synthesis of Stable γ‐CsPbI3 Perovskite Layers for Solar Cells Obtained by High Throughput Experimentation. Issue 22 (26th April 2019) - Becker, Pascal; Márquez, José A.; Just, Justus; Al‐Ashouri, Amran; Hages, Charles; Hempel, Hannes; Jošt, Marko; Albrecht, Steve; Frahm, Ronald; Unold, Thomas
Abstract: The structural phases and optoelectronic properties of coevaporated CsPbI3 thin films with a wide range of [CsI]/[PbI2 ] compositional ratios are investigated using high throughput experimentation and gradient samples. It is found that for CsI‐rich growth conditions, CsPbI3 can be synthesized directly at low temperature into the distorted perovskite γ‐CsPbI3 phase without detectable secondary phases. In contrast, PbI2 ‐rich growth conditions are found to lead to the non‐perovskite δ‐phase. Photoluminescence spectroscopy and optical‐pump THz‐probe mapping show carrier lifetimes larger than 75 ns and charge carrier (sum) mobilities larger than 60 cm 2 V −1 s −1 for the γ‐phase, indicating their suitability for high efficiency solar cells. The dependence of the carrier mobilities and luminescence peak energy on the Cs‐content in the films indicates the presence of Schottky defect pairs, which may cause the stabilization of the γ‐phase. Building on these results, p–i–n type solar cells with a maximum efficiency exceeding 12% and high shelf stability of more than 1200 h are demonstrated, which in the future could still be significantly improved, judging on their bulk optoelectronic properties. Abstract : Stable inorganic perovskite CsPbI3 thin films and solar cells are obtained by low temperature vacuum deposition without the need for high‐temperature annealing steps. Intentional compositional gradients on the samples allow combinatorial evaluation of structure‐property relationships using high‐throughput experimentation techniques, indicating that the perovskite phase is stable for Cs‐rich conditions. Solar cells with efficiency > 12% are demonstrated.